ANALISIS STRATEGI GURU DALAM MENERAPKAN PEMBELAJARAN MENDALAM BERBASIS VIDEO ANIMASI DI SD NEGERI 05 PERAWANG - Nurhazizah Ramla Susanti; Putri Octa Hadiyanti (STKIP Subang, 2026)
This research is motivated by the importance of implementing deep learning in the Merdeka Curriculum as a learning approach that can create an active, meaningful, and student-centered learning process. This study aims to analyze teachers' strategies in implementing deep learning based on animated videos in the IPAS subject for fourth-grade students at SD Negeri 05 Perawang. This research employed a qualitative approach with a descriptive research design. The research informants consisted of one fourth-grade teacher as the main informant and four students as supporting informants selected using purposive sampling. Data were collected through observation, interviews, and documentation. Data analysis used the Miles, Huberman, and Saldaña model, which includes data condensation, data display, and conclusion drawing and verification. Data validity was examined through source triangulation and technique triangulation. The results showed that the teacher had implemented deep learning strategies systematically through the stages of planning, implementation, and evaluation. In the learning process, the teacher utilized animated videos as learning media integrated with activities of understanding, applying, and reflecting. The use of animated videos helped students understand IPAS materials more concretely and interestingly while encouraging active participation throughout the learning process. The challenges encountered included limited facilities and infrastructure, differences in students' learning abilities, and limited learning time. These challenges were addressed through careful preparation of learning tools, the provision of alternative media, student assistance, and effective time management. Therefore, the teacher's strategy in implementing deep learning based on animated videos can create an active, interactive, meaningful, and student-centered IPAS learning process.